Inguinal draining-lymph node in 18F-FDG PET/CT images could be a new indicator for the diagnosis of fracture-related infection in the lower extremities - Wang, Yanbing; Sun, Zhenkui; Liang, Xiao; Shen, Chentian (Frontiers in Immunology, 2023)
Purpose The imaging diagnosis of fracture-related infection is often challenging. The aim of this study was to evaluate the value of 18 F-FDG PET/CT for the diagnosis of fracture-related infection (FRI) with internal fixation after orthopedic surgery in lower extremities.Methods A total of 254 consecutive patients who underwent 18 F-FDG PET/CT scans with suspected FRI with internal fixation in lower extremities were retrospectively investigated. 18 F-FDG PET/CT images were semiquantitatively evaluated with multiple metabolic parameters. Additionally, morphological information of the inguinal draining-lymph nodes (DLN) with the highest SUV value was also collected and analyzed.Results Patients were divided into two groups according to final diagnosis, namely infected (N=197) and non-infected group (N=57). The differences of the inguinal DLN related parameters including the long diameter, short diameter, maximum crosssectional area, maximum standardized uptake value (SUVmax), metabolic volume (MV) 60%, MV70%, MV80%, total lesional glycolysis (TLG) 60%, TLG70%, TLG80%, and the infection suspected area related parameters including SUVmax, MV25%, MV30%, MV35%, MV40%, MV50%, TLG70% between the two groups were statistically significant. We then compared the highest area under curves (AUCs) among morphological parameters of DLN, metabolic parameters of DLN and metabolic parameters of infection suspected area. The result demonstrated that SUVmax of the inguinal DLN showed the most excellent diagnostic performance with an AUC of 0.939 (P＜0.05).18 F-FDG PET/CT images could be a promising method for the diagnosis of suspected FRI with internal fixation after orthopedic surgery in lower extremities.